AB1223-HPR Personal Experiences of the 'Living Well with Arthritis' Self Management Course. (9th June 2015) - Druett, K.; Morris, M.; Minaur, N.; Silverthorne, C.
Abstract : Background: Recent research has identified the benefits of self-management programmes underpinned by cognitive behavioural approaches, including reduced fatigue, improved mood and improved quality of life (Hewlett et al., 2011). The "Living well with Arthritis" course was developed specifically for adults with inflammatory arthritis. This aimed to support adults in devloping self-managemnt skills in order to live well socially, physically and emotionally. The course content was adapted from a successful chronic pain programme. The course was co-delivered by a trained Patient Partner and a Clinical Psychologist to small groups over seven weekly 3 hour sessions. Topics included coping with fatigue, pain and stress, and communication skills. Objectives: To evaluate the patient's experience of the "Living Well with Arthritis" self-management programme and explore process factors associated with the development of self-management strategies. Methods: Five courses have been delivered over 2 years. All previous participants (30 patients) were invited to attend one of three focus groups, each lasting 90 minutes. Focus groups were employed because they facilitate participant interaction and reduce research influence. 14 women participated, with an average duration of inflammatory arthritis of 8 years. An interview guide was devised by the research team based on previous evaluations and with input from a patient partner. Results: Focus group evaluation identified a number of themes. These fell into two categories: processes within the course that helped "facilitate" and those which acted as "barriers" to adjusting to inflammatory arthritis. The facilitation themes included: "Meeting others" and feeling less isolated; "Making the invisible visible" identified an increased confidence in managing the invisibility of the condition through feeling validated, helping facilitate communication and pacing strategies. The "Patient Partner" was identified as helping to facilitate discussion. "Path to acceptance" reflected how aspects of the course had enabled increased acceptance and facilitated change: and underpinning this was the opportunity for "Emotional Processing". The second theme related to barriers and included: "Not enough time" to process more difficult emotions; "Slipping back" identified reasons why maintaining change could be a struggle; "Fighting it" and "Stigma" including factors that affected acceptance and difficulties making changes, alongise the identification of "additional stressors", such as financial loss. Conclusions: The focus groups produced a rich narrative surrounding process factors associated with the Living Well with Arthritis course. This included identifying factors which could facilitate the process of adapting to arthritis, such as the importance of social support in feeling understood and validated. This also identified factors which could act as barriers to change, such as needing more time for emotional processing. This evaluation has highlighted the value of an inflammatory arthritis specific self-management course as well as identified areas for further evaluation and development. References: Hewlett S et al. (2011). Self-management of fatigue in rheumatoid arthritis: a randomised controlled trial of group cognitive-behavioural therapy. Annals of the Rheumatic Diseases 70(6):1060-7. Disclosure of Interest: None declared